SURVEY OF BONE DENSITY IN PEOPLE OVER 40 YEARS OLD BASED ON T-SCORE (Vietnam Journal of Community Medicine, 2022)
Objectives: Survey of bone density in patients over 40 years old visiting the Department of Outpatientof VietDuc Hospital.Methods: Cross-sectional descriptive study, examining the bone density of 600 patients over 40years old by dual-energy X-ray absorptiometry (DEXA) at the lumbar vertebrae, femoral neck.Results: The rate of osteoporosis accounted for 37.33%, pre-osteoporosis 21.33%, of which theaverage bone density (T-score) was measured at L1, L2, L3, L4, left femoral neck (right) ) are: 0.079± 1.22 respectively; -0.23 ± 1.38; 0.01 ± 1.44; -1.13 ± 1.44; 0.22 ± 1.22 (0.35 ± 1.44). The averageT-score of men is higher than that of women. The mean T-score of the BMI
Keywords: Osteoporosis, DEXA, Bone density